Learning the language of earth science: Middle school students' explorations of rocks and minerals - Angelia Reid-Griffin (Lectito Journals, 2016)
The approaches and interpretations of a class of 6th graders and a class of 8th graders in a U.S. middle school asked to engage in tasks that involved using observations to describe and classify samples is the subject of this paper. Overall 8th graders were better able to perform the tasks, suggesting a developmental advantage aspect. However, the descriptions of the rock and mineral samples recorded by students can be considered salient for identification purposes. However, the descriptions were not recognized as salient features by most of the grade 6th and 8th U.S. students.